Cosmological Implications of Affine Gravity - Azrı, Hemza; Azri, Hemza; Demir, Durmuş Ali (Izmir Institute of Technology, 2018)
The main aim of this thesis is to reveal some interesting aspects of the purely affine theory of gravity and its cosmological implication. A particular attention will be devoted to its consequences when applied to cosmological inflation. Primarily, affine spacetime, composed of geodesics with no notion of length and angle, accommodates gravity but not matter. The thesis study is expected to reveal salient properties of matter dynamics in affine spacetime and may reveal an intimate connection between vacuum state and metrical gravity. An interesting application of the framework is the inflationary regime, where it is shown that affine gravity prefers only a unique metric tensor such that the transition from nonminimal to minimal coupling of the inflaton is performed only via redefinition of latter. This allows us to avoid the use of the so called conformal frames. In fact, unlike metric gravity, the metric tensor in affine gravity is generated and not postulated a priori, thus this tensor is absent in the actions and conformal transformation does not make sense. Last but not least, we try to show how metric gravity can be induced through a simple structure that contains only affine connection and scalar fields. General relativity arises classically only at the vacuum, and this view of gravity may be considered as a new way to inducing metric elasticity of space, not through quantum corrections as in standard induced gravity, but only classically. The thesis is concluded by analyzing affine gravity in a particular higher-dimensional manifold (product of two spaces) in an attempt to understand both, the cosmological constant and matter dynamically.

Bu tezin temel amacı yalnızca afin teoresini içeren gravitasyon kurumanın ve onun kozmolojik uygulamalarının bazı ilginç yönlerini açığa çıkartmaktır dikkatimizi özellikle bu kuramın kozmolojik enflasyona uygulandığı zamanki sonuçlarına vereceğiz. Öncelikle belirtmek gerekir ki uzunluk ve açı kavramları olmaksızın jeodeziklerden oluşmuş afin uzay zamanı gravitasyon ile ilintili olup maddeyi kapsamaz. Bu tez çalımasından afin uzay zamanında madde dinamiğinin göze çarpan özelliklerini göstermesi beklenmektedir ve bu çalışma metriksel gravitasyon ile vakum hali arasındaki yakın ilişkiyi ortaya koyabilir. Çalışmanın dikkat çekici bir uygulaması enflasyon rejimidir. Burada afin gravitasyonun sadece kendine özgü bir metrik tensörü tercih ettiği gösterilmiştir. Öyle ki inflatonun minimal almayan bağlaşımdan minimal olana geçişi sadece inflatonun yeniden tanımlanması vasıtasıyla gerçekleştirilir. Bu bize konformal çerçevelerden kaçınmamız için imkan sağlamıştır. Aslında, metrik gravitasyonunun aksine, afin gravitasyondaki metrik tensör üretilmiş olup, öncelikli olarak pöstüle edilmemiştir, bu nedenle bu tensör aksiyonlarda görünmemektedir ve konformal dönüşüm bir anlam ifade etmemektedir. Sonuncu ama son derece önemli noktalardan bir tanesi de, sadece afin bağlantısı ve skaler alanları içeren basit bir yapı üzerinden metrik gravitasyonunun nasıl indüklendiğini göstermeye çalıştık. Genel görecelilik klasik olarak sadece vakumda meydana gelmiştir ve gravitasyonun bu görünüşü, standart indüklenmiş gravitasyondaki kuantum düzeltmeler aracılığıyla olmadan, sadece klasik olarak uzayın metrik elastikiyetini oluşturmak için yeni bir yol olarak göz önünde bulundurulabilir. Bu tez, dinamiksel olarak madde ve kozmolojik sabitin her ikisini de anlamak amacıyla, daha yüksek boyutlu belirli bir manifold içerisinde afin gravitasyonunu inceleyerek sonuçlandıracaktır.
Kütle ve Çekiminin Kozmolojik Uygulamaları
Thesis (Doctoral)--Izmir Institute of Technology, Physics, Izmir, 2018
Includes bibliographical references (leaves: 120-128)
Text in English; Abstract: Turkish and English
Keywords: Affine gravity; Induced gravity; Vacuum energy; Inflation